A Simple Model of Tax-Favored Retirement Accounts - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2009)
To defend myopic workers against themselves, the government introduces a mandatory system but to help savers, it adds tax-favored retirement accounts. In a very simple model, where benefits are proportional to contributions, we compare three extreme systems: (i) the pure mandatory system, (ii) the asymmetric system, where only the savers participate in the voluntary system, (iii) the symmetric system, where both types participate proportionally to their wages. The symmetric voluntary system is welfare-superior to the asymmetric one as well as to the pure mandatory system, which in turn are equivalent to each other.
Keywords: H55; D91; 330; mandatory pensions; tax-favored retirement accounts; voluntary contributions; subsidies; Altersvorsorge; Gesetzliche Rentenversicherung; Private Altersvorsorge; Steuervergünstigung; Theorie